2022
DOI: 10.1186/s13041-022-00923-w
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral contributions of T-type calcium channels in pain

Abstract: Chronic pain is a severely debilitating condition that reflects a long-term sensitization of signal transduction in the afferent pain pathway. Among the key players in this pathway are T-type calcium channels, in particular the Cav3.2 isoform. Because of their biophysical characteristics, these channels are ideally suited towards regulating neuronal excitability. Recent evidence suggests that T-type channels contribute to excitability of neurons all along the ascending and descending pain pathways, within prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 160 publications
0
21
0
2
Order By: Relevance
“…Future studies in preclinical epilepsy models are needed to assess whether GPR55 and T-type calcium channels are necessary for the anticonvulsant effect of these phytocannabinoids. It would also be interesting to explore the effects of these phytocannabinoids in other disease models in which T-type channels and GPR55 play a role, such as in models of insomnia, pain, and gastrointestinal disorders ( Harding and Zamponi, 2022 ). Given the promiscuity of the phytocannabinoids, additional cellular pharmacology studies are needed to address whether CBGVA and CBDVA affect other phytocannabinoid targets such as cannabinoid receptors and transient receptor potential (TRP) channels.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies in preclinical epilepsy models are needed to assess whether GPR55 and T-type calcium channels are necessary for the anticonvulsant effect of these phytocannabinoids. It would also be interesting to explore the effects of these phytocannabinoids in other disease models in which T-type channels and GPR55 play a role, such as in models of insomnia, pain, and gastrointestinal disorders ( Harding and Zamponi, 2022 ). Given the promiscuity of the phytocannabinoids, additional cellular pharmacology studies are needed to address whether CBGVA and CBDVA affect other phytocannabinoid targets such as cannabinoid receptors and transient receptor potential (TRP) channels.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage‐gated calcium channels (VGCCs; Cas) are a promising target for the treatment of chronic pain due to their role in regulating neuronal excitability and facilitating synaptic vesicle release at primary afferent synapses (Harding & Zamponi, 2022). First‐order neurons transmit nociceptive information from peripheral tissue into the dorsal horn of the spinal cord, where neurotransmission onto dorsal horn neurons is predominantly facilitated by two presynaptic VGCCs: Ca v 2.2 (N‐type) and to a lesser extent Ca v 3.2 (T‐type) channels (Zamponi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The T-type calcium Cav3.2 isoform regulates the neuronal response to pain. 52,53 Cav3.2 knockout models and mice pretreated with Cav3.2 blockers showed impaired nociceptive response to pain stimuli. 54 Previous reports indicated that the antinociceptive action of arachidonic compounds involves inhibition of Cav3.2 channels, suggesting a potential interaction between Cav3.2 and AM404.…”
Section: Downstream Targets Of Trpvmentioning
confidence: 99%